Juridical Analysis Awareness of Profession Advocacy to Financial Transaction Reports and Analysis Centre (PPATK) During Prevent and Eradicate Money Laundering Crime - Wisnu Firmansyah; Hendra Tanu Atmadja (Journal of Multidisciplinary Academic, 2021)
An advocate is a professional who to provide litigation and non-litigation legal services in accordance with the term of the applicable laws and regulations. In this case, advocates might be paid an honorarium or fee from their clients in order to carry out their profession, alluded to in the Law on Advocates. In line to money laundering, the government in this case broadens the scope of the perpetrators of money laundering crimes, making the advocate profession a reporting party to their clients to Financial Transaction Reports and Analysis Centre (PPATK) in accordance with advocates who oppose to the presence of the Government Regulation by petitioning the Supreme Court for a Judicial Review. The question is whether money laundering may be executed at an attorney’s fee and whether Government Regulation No. 43 of 2015 violates the Advocates Law (Case Study on Supreme Court Decree No. 51p/HUM/2015)? This research is normative legal research that uses a qualitative normative approach. The results of this study indicate that the crime of money laundering cannot be carried out on an advocate fee as long as it meets morality and is determined fairly based on the agreement of both parties as stipulated in Article 1320 of the terms of the validity of the agreement. However, it is possible to be subject to the crime of money laundering if the person concerned intentionally agrees with his client to deposit the authorized amount of money with his lawyer in the context of committing the crime of money laundering. Even with the rejection of the applicant’s application with the Supreme Court Decree No. 51p/HUM/2015 in terms of Government Regulation No. 43 of 2015 which is considered to have conflicted with Article 19 of the Law on Advocate with regard to the confidentiality of their clients. Shows that the advocate profession is obliged as a reporting party to PPATK who with legal awareness must report related to suspicious financial transactions by their clients.